2015
DOI: 10.1523/jneurosci.3816-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin Induces Presynaptic Depression of D2 Dopamine Autoreceptor-Mediated Neurotransmission in Midbrain Dopaminergic Neurons

Abstract: Increased dopaminergic signaling is a hallmark of severe mesencephalic pathologies such as schizophrenia and psychostimulant abuse. Activity of midbrain dopaminergic neurons is under strict control of inhibitory D 2 autoreceptors. Application of the modulatory peptide neurotensin (NT) to midbrain dopaminergic neurons transiently increases activity by decreasing D 2 dopamine autoreceptor function, yet little is known about the mechanisms that underlie long-lasting effects. Here, we performed patch-clamp electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 55 publications
3
46
0
Order By: Relevance
“…Pre-incubation with the non-selective NT type 1/2 receptor antagonist SR 142948 prevented LTDDA (Figure 2 A 1-2, F; one-way ANOVA, F4,26 = 18.92, p < 0.0001, Tukey's, p = 0.0001). Conversely and consistent with our previous findings (Piccart et al, 2015), a selective NT type-1 receptor antagonist failed to prevent LTDDA (Figure 2 B 1-2, F; p = 0.99). As presumably only dopamine neurons are being depolarized by the blue light, this suggests that dopamine neurons are themselves releasing NT that induces LTDDA though activation of NT type-2 receptors.…”
Section: Ltdda Requires Nt Type-2 Receptor Signaling and Postsynaptisupporting
confidence: 93%
See 3 more Smart Citations
“…Pre-incubation with the non-selective NT type 1/2 receptor antagonist SR 142948 prevented LTDDA (Figure 2 A 1-2, F; one-way ANOVA, F4,26 = 18.92, p < 0.0001, Tukey's, p = 0.0001). Conversely and consistent with our previous findings (Piccart et al, 2015), a selective NT type-1 receptor antagonist failed to prevent LTDDA (Figure 2 B 1-2, F; p = 0.99). As presumably only dopamine neurons are being depolarized by the blue light, this suggests that dopamine neurons are themselves releasing NT that induces LTDDA though activation of NT type-2 receptors.…”
Section: Ltdda Requires Nt Type-2 Receptor Signaling and Postsynaptisupporting
confidence: 93%
“…We previously found that stimulation-induced long-term depression of D2-IPSCs (LTDDA, Beckstead and Williams, 2007) is driven by endogenous NT signaling (Piccart et al, 2015) and suggested that dopamine neurons might also release NT. Thus, to determine the source of NT which drives LTDDA we used a combination of transgenic and optogenetic tools to delineate the role of dopamine neurons and NT afferents to the midbrain.…”
Section: Repetitive Stimulation Of Dopamine Neurons Is Sufficient To mentioning
confidence: 99%
See 2 more Smart Citations
“…Since NtsR1 is a Gα q -coupled GPCR (Tanaka et al, 1990), our findings indicate a mechanism for Nts to directly enhance the activation of NtsR1-expressing DA neurons, consistent with the established roles for NtsR1 in promoting DA release to the striatum and DA-mediated locomotor activity (Remaury et al, 2002; Steinberg et al, 1994), anorexia (Remaury et al, 2002), and reward (Kempadoo et al, 2013; Rouibi et al, 2015) Our data do not, however, rule out roles for the non-DAergic populations of NtsR2 cells to indirectly promote DA signaling. The TH-negative NtsR2 neurons found primarily within the ventromedial, GABA-rich portion of the VTA may disinhibit local DA neurons and promote their activation (Kempadoo et al, 2013; Piccart et al, 2015). Nts may also act via the numerous NtsR2-expressing astrocytes within the VTA to indirectly modify DA-mediated behavior, consistent with reports of glial cells mediating NtsR2-dependent fear behavior (Yamauchi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%